Saddle preferences and perceived comfort of competitive women cyclists - Herrero-Molleda, A.; Bini, R.; García-López, J. (Science & Sports, 2024)
Objectives Women experience more saddle-related pain during cycling compared to men. However, there is a lack of research focused on the optimal saddle for this population. Therefore, the aim of this study was to analyze the most used type of saddle (i.e., women's saddles, men's saddles or unisex) and the effect of saddle type on perceived comfort in elite women road cyclists.